Assessment of Head Tremor with Accelerometers Versus Gyroscopic Transducers. Issue 2 (8th July 2016) - Elble, Rodger J.; Hellriegel, Helge; Raethjen, Jan; Deuschl, Günther
Abstract: Background: Accelerometers and gyroscopes are used commonly in the assessment of hand tremor, but their validity in the assessment of head tremor has not been studied. We hypothesized that gyroscopy would be superior to accelerometry because head tremor is rotational motion, and gyroscopes record rotational motion, free of gravitational artifact. We also hypothesized a strong logarithmic relationship between 0 to 4‐point tremor ratings and the transducer measures of tremor amplitude, similar to those previously reported for hand tremor. Methods: Head tremor was recorded for 1 minute in each of the five head positions used in the Essential Tremor Rating Assessment Scale, using a triaxial accelerometer and triaxial gyroscope mounted at the vertex of the head. Mean and maximum 3‐second burst displacement tremor and rotation tremor were computed by spectral analysis. The minimum detectable change for the transducers was estimated using the residual mean squared error from repeated‐measures analysis of variance. Results: Tremor displacement and rotation (T) were logarithmically related to tremor ratings (tremor rating score; TRS): log(T) = α TRS + β, where α ≈ 0.47 for displacement and ≈0.64 for rotation, and β ≈ −1.8 and −1.4. Tremor ratings correlated more strongly with gyroscopy (r = 0.83–0.87) than with accelerometry (r = 0.71–0.75). Minimum detectable change (percent reduction) was approximately 66% of the baseline geometric mean. Conclusions: Gyroscopic transducers are superior to accelerometry for assessment of head tremor. Both measures of head tremor are logarithmically related to tremor ratings. The minimum detectable change of the transducer measures is comparable to those previously reported for hand tremor.